Pengembangan Media Project Based Online Learning pada Kompetensi Teknologi Informasi dan Komunikasi (TIK) bagi Siswa SMP - Mustaji; Achmad Noor Fatirul; Tiono Setyawan (Universitas Kanjuruhan Malang, 2021)
This goal of the study is to produce a website-based online learning media in a Project-based Online Learning setting that is appropriate for students of SMPN 1 Mojokerto. The researcher applied the DDDE model (Decide, Design, Develop, and Evaluate) ) to develop the media. To validate the Learning media, learning material experts and media / learning design experts are involved. To trial the media, the small-scale trial was conducted by 3 peer teachers and the large-scale trial was carried out by 32 students. The test subjects were determined by purposive random sampling technique. In collecting data, the researcher adressed questionnaires to test subject. The result was collected and it was analized descriptively. The validation results from the experts were 95% and the material experts were 90% that is indicating that the media is very appropriate for learning. The results of small-scale trial was 90.8% and large-scale trial was 89.5%. This means website-based online learning media in a Project-Based Online Learning setting is appropriate for SMPN 1 Mojokerto Students.